2020
DOI: 10.3390/ani10071150
|View full text |Cite
|
Sign up to set email alerts
|

The Study of the Response of Fat Metabolism to Long-Term Energy Stress Based on Serum, Fatty Acid and Transcriptome Profiles in Yaks

Abstract: Long-term energy stress (ES) during the cold season is a serious problem for the breeding of yaks. In this paper, the response of fat metabolism in yaks to long-term ES during the cold season was studied. Gas chromatography (GC) analysis showed that the percentage of saturated fatty acids (SFAs) in the subcutaneous fat of the yaks in the ES group was 42.7%, which was less than the 56.6% in the CO group (p < 0.01) and the percentage of polyunsaturated unsaturated fatty acids (PUFAs) in the subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The metabolism of lipids, carbohydrates, and energy, all related with feed energy utilization and storage, was enhanced in grazing yaks when compared with the feedlot cattle in this study. Through long-term adaptations to energy stress, yaks have evolved traits of slow fat mobilization and strategies to conserve energy in the harsh alpine environment ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of lipids, carbohydrates, and energy, all related with feed energy utilization and storage, was enhanced in grazing yaks when compared with the feedlot cattle in this study. Through long-term adaptations to energy stress, yaks have evolved traits of slow fat mobilization and strategies to conserve energy in the harsh alpine environment ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…OXSM is a 3-oxyacyl -[acyl carrier protein] synthase. Xiong et al (2020) found that OXSM has inhibitory effects on fat catabolism, fat anabolism, and fatty acid oxidation, and promotes glycerol transport and polyunsaturated fatty acid synthesis. MCAT is also an important gene involved in lipid metabolism ( Ghadge et al, 2020 ).…”
Section: Discussionmentioning
confidence: 97%
“…That the expression of FADS1 in the lower adipose tissue of the cowhide is up-regulated under cold stimulation conditions. This promotes the production of polyunsaturated fatty acids in the lower adipose of the cowhide 45 . It was also confirmed in pigs and cattle 46 , 47 .…”
Section: Discussionmentioning
confidence: 99%